Gender differences in perceived stigma and hope in people living with HIV / AIDS: an exploratory study - Chivate, Prachi; Umate, Maithili; Nimkar, Swateja; De Sousa, Avinash (International Journal Of Community Medicine And Public Health, 2017)
Background: Stigma is a major hurdle in overcoming the HIV epidemic and affects almost all people living with HIV/AIDS (PLWHA). In India, though majority of PLWHA are men, gender gap is narrowing with rates of infection increasing in women, most commonly due to transmission from their partners. Gender inequality in social and economic context leads women to vulnerability. The purpose of this study was to assess gender differences in the perceived stigma and hope in PLWHA, and to study the correlation of perceived stigma with hope and age in this population. Methods: The sample was 68 HIV patients attending HAART clinic of a tertiary government hospital. Patients were assessed using Barbara Berger stigma scale and Herth hope index, and their scores were subjected to inferential statistical methods such as t-tests and correlation analysis. Results: Although there are no gender differences in perceived stigma, there is an inverse relationship of many components of perceived stigma with hope in women. It was also found that women members of PLWHA group feel significantly less hopeful than men. Age was noted to have an inverse relationship with perceived stigma in men. Conclusions: Greater attention is warranted to this growing proportion of HIV positive women in health policies and to alleviate their suffering which is multiplied as being socially disadvantaged due to their gender. This study highlights the need of special attention to women with HIV in health settings. Further research is needed to understand the relation of social support and depression with perceived social support.